Arrhenatherum elatius ssp. bulbosum Revisited – A Practical Approach to Decode Past Plant-related Activities. (2nd January 2021) - Effenberger, Henrike; Nickol, Martin; Kirleis, Wiebke
ABSTRACT: The charred bulbs of tuber oat grass ( Arrhenatherum elatius ssp. bulbosum ) are found in different archaeological contexts from various periods all over Europe. However, following the pre-Roman Iron Age, the occurrence of the plant gets scarcer. To understand why and how the bulbs of tuber oat grass have entered the archaeological record, it is crucial to study the habitus and the ecology of the plant. Therefore, growing, drying, charring and consumption experiments were carried out between 2012 and 2014. The empirical data from these experiments contributes to gaining a better understanding of subsistence practices and food choices in past societies.